The Differences of Lexical Hedges Used by Male and Female Participants in NUDC And WUDC 2021 - Anisa Putri Utami; Ririn Putri Ananda; Ria Anggraini; Washlurachim Safitri (English Education Study Program Faculty of Teacher Training and Education, 2022)
Hedges has received much attention in relation to conversational rules as a mean to facilitate turn-taking, politeness, mitigate face-threats, but it is also considered a means of conveying vagueness purposely. The aim of this study is identify the lexical hedges are used by male and female participants in NUDC and WUDC 2021. This research was qualitative research. The object of this research was the recording of NUDC 2020 and WUDC 2021 debate accessed from youtube. The researcher used table checklist as the instrument of this research. There were two findings of this research; (1) The lexical hedges made by male participants in NUDC and WUDC 2021 were modal auxilary verb, lexical verb, probability adjective, adverb, adverb of frequency, if clause, compound hedges, and fillers; (2) The lexical hedges made by female participants in NUDC and WUDC 2021 were modal auxilary verb, lexical verb, probability adjective, noun, adverb, adverb of frequency, compound hedges, and fillers. To conclude, male and female participants made many kinds lexical hedges in NUDC and WUDC 2021. It was suggested for further research to conduct another research in the same field to this present research about the use of lexical hedges among the male and female students in more wide sample and deep data analysis.